Behavioral Evidence and Olfactory Reception of a Single Alarm Pheromone Component in Halyomorpha halys - Zhong, Yong-Zhi; Tang, Rui; Zhang, Jin-Ping; Yang, Shi-Yong; Chen, Guo-Hua; He, Kang-Lai; Wang, Zhen-Ying; Zhang, Feng (Frontiers in Physiology, 2018)
Halyomorpha halys is a major herbivore insect in the fruit orchards of China that has become a devastating invasive pest in North America and Europe since its accidental introductions in the 1990s and 2000s, respectively. Like other hemipteran insects, H. halys releases defensive chemicals against natural enemies, including (E)-2-decenal, which is an aldehyde associated with alarm pheromones. In this study, a series of electrophysiological and behavioral tests were conducted to characterize the alarm functions of (E)-2-decenal among H. halys adults and nymphs. An antennal transcriptome was obtained from a Chinese H. halys population, and 44 odorant-binding protein (OBP) genes were annotated. Among them, five putative alarm pheromone-binding proteins were screened and were extremely consistent with their homologs from US populations. These five OBPs were later expressed in a heterologous expression system, harvested, and then challenged with (E)-2-decenal in a binding assay. All five OBPs showed high binding activities to (E)-2-decenal, which demonstrated its behavioral significance as a defensive component in H. halys, as well as being the first report of its olfactory reception. These findings will help develop behavioral-mediating tools as part of integrated pest management approaches to control this invasive pest.